2018
DOI: 10.2337/dc18-0706
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Modulation of Hepatic Glucose Production With Insulin Glargine U300 and Glargine U100 at Steady State With Individualized Clinical Doses in Type 1 Diabetes

Abstract: OBJECTIVE This study characterized the pharmacokinetics (PK), pharmacodynamics (PD), and endogenous (hepatic) glucose production (EGP) of clinical doses of glargine U300 (Gla-300) and glargine U100 (Gla-100) under steady-state (SS) conditions in type 1 diabetes mellitus (T1DM). RESEARCH DESIGN AND METHODS T1DM subjects (N = 18, age 40 ± 12 years, T1DM duration 26 ± 12 years, BMI 23.4 ± 2 kg/m2, A1C 7.19 ± 0.52% [55 ± 5.7 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(87 citation statements)
references
References 31 publications
3
83
0
Order By: Relevance
“…Subjects, study design, and methods have been previously described in detail. 3 In brief, 18 persons with T1DM (age 40 -12 years, diabetes duration 26 -12 years, body mass index 23.4 -2 kg/m 2 , A1C 7.19% -0.52% [55 -6 mmol/ mol], plasma C-peptide 0.01 -0.01 ng/mL) were studied after 3 months of optimization of glycemic control with Gla-300 or Gla-100 (evening dosing), titrated to fasting Section of Endocrinology & Metabolism, Department of Medicine, Perugia University School of Medicine, Perugia, Italy. Preliminary data from this study were submitted to the 77th Scientific Sessions (2017), June 9-13, 2017, San Diego, California, and has been accepted for poster presentation with abstract publication in Diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjects, study design, and methods have been previously described in detail. 3 In brief, 18 persons with T1DM (age 40 -12 years, diabetes duration 26 -12 years, body mass index 23.4 -2 kg/m 2 , A1C 7.19% -0.52% [55 -6 mmol/ mol], plasma C-peptide 0.01 -0.01 ng/mL) were studied after 3 months of optimization of glycemic control with Gla-300 or Gla-100 (evening dosing), titrated to fasting Section of Endocrinology & Metabolism, Department of Medicine, Perugia University School of Medicine, Perugia, Italy. Preliminary data from this study were submitted to the 77th Scientific Sessions (2017), June 9-13, 2017, San Diego, California, and has been accepted for poster presentation with abstract publication in Diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…R ecent studies have compared the pharmacokinetics (PK) and pharmacodynamics (PD) of the long-acting (basal) insulin analogues glargine U300 (Gla-300) and glargine U100 (Gla-100) in type 1 diabetes mellitus (T1DM) at fixed insulin doses after single injection, 1 at steady state, 2 and at individual doses that persons with T1DM require daily. 3 In addition to glucose metabolism, insulin regulates several physiological pathways, such as modulation of glucagon secretion, 4 effects on lipid 5 and protein 6 metabolism, and endothelial function. 7 Only one study, investigating PK/PD of glargine and detemir at steady state in T1DM, however, has reported on the effects of long-acting insulin analogues, on regulation of alanine, lactate, and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin glargine 300 units/mL (Gla‐300) has shown low within‐ and between‐day glycaemic variability, with a flatter, more stable pharmacokinetic profile and less fluctuation in glycaemic control compared with insulin glargine 100 units/mL (Gla‐100) or insulin degludec 100 units/mL . Importantly, Gla‐300 has been associated with less within‐day variability in patients with T1D, with duration of insulin action exceeding 24 hours at steady state with clinical, individual doses . Furthermore, in a pharmacokinetic/pharmacodynamic study of patients with T1D, Gla‐300 was shown to have a longer duration of action than the same dose of Gla‐100.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Importantly, Gla-300 has been associated with less within-day variability in patients with T1D, with duration of insulin action exceeding 24 hours at steady state with clinical, individual doses. 11 Furthermore, in a pharmacokinetic/pharmacodynamic study of patients with T1D, Gla-300 was shown to have a longer duration of action than the same dose of Gla-100. Doses may not be representative of randomized clinical trials as higher doses of Gla-300 were required for participants in the EDITION phase 3 clinical trial in patients with T1D.…”
Section: Introductionmentioning
confidence: 99%